Aptamer Functionalized Upconversion Nanotheranostic Agent With Nuclear Targeting as the Highly Localized Drug-Delivery System of Doxorubicin - Song, Xinyue; Yan, Tao; Tian, Feng; Li, Fengyan; Ren, Linlin; Li, Qiong; Zhang, Shusheng (Frontiers in Bioengineering and Biotechnology, 2021)
As a widely used anti-cancer drug, doxorubicin (DOX) could induce cell death mainly via interfering with DNA activity, thus, DOX could perform therapeutic effects mainly in cell nucleus. However, most of the reported drug delivery systems lacked the well localization in the nucleus and released DOX molecules into the cytoplasm. Due to formidable barriers formed in the nuclear envelope, only around 1% of DOX could reach the nucleus and keep active. Therefore, DOX molecules were inevitably overloaded to achieve the desired therapeutic efficacy, which would induce serious side-effects. Herein, we developed a highly-localized drug nanocarrier for in-situ release of DOX molecules to their action site where they could directly interfere with the DNA activity. In this work, we used cationic polymer modified upconversion nanoparticles (UCNPs) as the luminescence core and gene carrier, while aptamers served as the DNA nanotrain to load DOX. Finally, the prepared nanotheranostic agent displayed good targetability, high cell apoptosis ratio (93.04%) with quite lower concentration than the LC50 of DOX, and obvious inhibition on tumor growth.